Perancangan Prototype Sistem Manajemen Rekam Medis Konvensional Berbasis Barcode - Yunifa, Nayada Ilfania Arokhta; Ikawati, Fita Rusdian; Afifah, Lilik; Kusumawati, Atik (Politeknik Negeri Jember, 2025)
The management of conventional medical record files in healthcare facilities often faces challenges related to document tracking, file distribution, and operational inefficiency, which can lead to service delays and compromise data integrity. Similar issues occur at the Islamic Hospital of UNISMA Malang, where medical record files are often unavailable in the archive room, scattered across doctors’ offices, borrowed by other units, or not returned even after treatment is completed. This study aims to design a barcode-based prototype system for managing conventional medical records to address these challenges and enhance management efficiency. The design process adopted a comprehensive prototyping approach, including requirement communication, rapid planning, design modeling (Entity-Relationship Diagram, Use Case Diagram, and Activity Diagram), and the development of an interactive prototype using Figma. The proposed system provides essential functions such as accurate document tracking through barcode scanning for borrowing, returning, and shelving records. It also integrates an internal communication module to facilitate smooth collaboration among medical staff and a Tracer feature to monitor file movements. The prototype shows significant potential to improve tracking efficiency, data accuracy, and inter-unit coordination, ultimately contributing to more effective patient care.